Penerapan Metode Vikor Dalam Pengambilan Keputusan Penunjukan Kader Pemberian Obat Pencegahan Massal Filariasi Studi Kasus Dinas Kesehatan Aceh Singkil - Enci Manda Sari (STMIK Budi Darma, 2021)
The Cadre Officer for the Provision of Mass Prevention of Drugs is an employee recruited from the Aceh Singkil Health Office, for the community, who is tasked with assisting the smooth running of health services. Filariasis is a negleted tropical disease (NTD) which has a severe impact on the patient because it causes disability. Because filariasis causes permanent disability and causes misery to the community, prevention is carried out by administering Filariasis Mass Prevention Drugs. Provision of Mass Prevention Drugs for filariasis is carried out by giving mass drugs once a year for five consecutive years by cadre officers for Mass Preventive Drug Administration. The problem in the formation of cadre officers so far is that the Aceh Singkil Health Service is still lacking, because so far the selection of cadres for Mass Prevention Drugs is still done manually by the committee in making decisions on cadres of giving Mass Prevention Drugs for Filariasis so that it can be fatal, because those who have been elected training was carried out by the Aceh Singkil Health Office so that when conducting training many were considered inappropriate. To overcome this problem, a decision was made by the cadre officer for the provision of Mass Prevention Drugs for Filariasis by using the computer-based Vikor method based on the criteria set by the Aceh Singkil Health Service so that in making decisions it does not result in errors and performance to select cadre officers for Mass Prevention Drugs. fast